A Practical Guide for Plagiarism Detection Through the Coordinated Use of Software and (Human) Hardware - Misra, Durga Prasanna (Journal of Gastrointestinal Infections, 2022)
Duplication of content, whether it be text, figures, tables, or ideas, without duly referencing the original source of such content is called as plagiarism. Plagiarism of text can be flagged by similarity checking software. Careful curating of content before it is put into similarity checking software for screening as well as a thorough understanding of how such software works are essential to appropriately interpret such similarity check reports. Mere similarity is not plagiarism. Drawing an inference regarding plagiarism based on the output of similarity checking software requires considerable human input from editors and reviewers. Identification of plagiarism of figures, tables, and ideas almost entirely depends on the efforts of editors or reviewers rather than being detectable automatically. A thorough understanding of plagiarism is essential for prospective authors to safeguard against this academic sin.
Keywords: iThenticate; plagiarism; publication ethics; similarity